Diterpene pekinenal from euphorbia pekinensis radix induced IEC-6 cells apoptosis mediated by mitochondria and death receptors. (June 2019) - Yao, Fang; Jiang, Dongjing; Cheng, Fangfang; Yao, Weifeng; Chen, Peidong; Guo, Shuchen; Cao, Yudan; Zhang, Li
Abstract: Pekinenal, a diterpenoid from the roots of Euphorbia pekinensis Rupr., can cause serious intestinal toxicity. However, its toxic mechanism hasn't been comprehensively understood. This present study aims to clarify its toxic effects and investigate the potential mechanism. In vitro effects of pekinenal on cell proliferation, cell cycle and apoptosis were examined by performing experiments on rat intestinal crypt epithelial cells (IEC-6). Proteins and enzymes involved in cell apoptotic pathways were detected by Western blot and enzyme-linked immunosorbent assay (ELISA), and related mRNAs were detected by RT-PCR. The results showed that the cell cycle was arrested in G0/G1 phase, and apoptotic morphology changes in pekinenal-treated cells. Furthermore, pekinenal up-regulated the expression level of apoptotic protein including Bax, AIF, Apaf-1 and the expression level of mRNA such as Fas, FasL, TNFR1 and NF-κB, while down-regulated the expression level of Bcl-2, ultimately triggering the apoptosis of caspase dependence. In conclusion, the above data confirmed that pekinenal inhibited the proliferation of IEC-6 cells and induced cells apoptosis by modulating mitochondrial and death receptor pathways. Graphical abstract: Unlabelled Image Highlights: Pekinenal compound was evaluated in rat intestinal cell line IEC-6. Pekinenal compound was cytotoxic to IEC-6 cells. Pekinenal compound induced IEC-6 cells apoptosis by modulating Mitochondrial or death receptor pathways